Ayat-Ayat Tentang Kisas Dalam Perspektif Ibnu Katsir Dan Fazlur Rahman - Akbar, Padil; N, Abd. Muid; Rofiah, Nur; Uzm, Bil (Jurnal Global Ilmiah, 2025)
This study examines the concept of kisas (reciprocal retribution) in the Qur'an, seen from the perspective of two prominent commentators: Ibn Katsir (a classical commentator) and Fazlur Rahman (a contemporary commentator). This research aims to understand the similarities and differences in their interpretation of the Qur'anic verses about the kisas. This study uses the maudhu'i (thematic) tafsir method with an analytical-comparative approach. The research data is in the form of Qur'anic verses related to Kisas interpreted by Ibn Kathir in the book Tafsir Ibn Kathir and Fazlur Rahman in his double movement thinking method. This research is motivated by the existence of pros and cons in society regarding the punishment of kisas (commensurate retribution). This research is intended to answer questions about the law and interpretation of the kisas in the Qur'an, also explain the comparative analysis of Ibn Kathir and Fazlur Rahman's interpretation of the verses of the kisas, as well as to find out the text and context of the verses about the laws of kisas by using the double movement method to analyze the comparative interpretation of Ibn Kathir and Fazlur Rahman. The results of this research are expected to provide an overview of the interpretation of Kisas in the treasures of Islamic interpretation. It is also hoped that it can bring out a more comprehensive and contextual understanding of the application of Kisas in the modern era.